Produktivitas Kerja Karyawan Umkm Dimasa Pandemi Covid-19 Melalui Lingkungan Kerja, Motivasi Dan Pengalaman Kerja - Tony Susilo Wibowo; Christina Menuk Srihandayani; Ade Radita Sari (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background - Qualified personnel are one of the most significant things that the firm must hold in order to achieve the desired vision for work productivity. Aim - The purpose of this study is to assess the impact of the work environment, motivation, and work experience on employee productivity at SME Aji Batara Perkasa Mandiri. Design/Methodology - This study necessitates a quantitative approach, with 74 employees serving as a sample. Purposive sampling was employed as a sample strategy. A questionnaire was used to gather data, and the instrument was then assessed for validity and reliability. The requirements test was performed first, followed by the hypothesis test, before completing multiple linear regression analysis. Findings - The study's findings suggest that the work environment, motivation, and work experience all contribute to SME employees' increased productivity during the Covid-19 epidemic. Research implication - The work environment must be examined in order to preserve the comfort and safety of the workplace by adhering to the health protocol regulations. Limitations - The scope of this research is limited to one SME, thus it cannot reflect the situation in other SMEs in the same area.